(untitled) (New York, 1995)
The book offers the knowledge about the chemistry of life. It is desugned to guide students through the challenging material needed to master the study of biochemistry by systematically dividing the daunting task of learning a large quantity of information into more manageable tasks. Each chapter of the book consists of: *) An introduction that puts the material in the context, emphasizes key ideas, and pffers a quick, accessible summary. *) Learning objectives that set small goals to research, organized by topic and cross-referenced to the text, highlight important definitions. *) A self-test keyed to corresponding sections in the text. *) A problems section that supplements problems in the text, providing practice in applying concepts. *) Answers to both the self-test and the problems. *) Expanded solutions to text problems that explain in greater detail the short answers in the text. An Glossary at the end of the book provides clear and concise definitions of hundreds of terms from the text
Keywords: Biochemistry,Human physiology